Opportunities and Challenges of Nurses after Upgradation of Class 2 Status (Bangladesh Journal of Medical Education, 2022)
Nurse’s job facilities and challenges have emerged as a burning issue in health care delivery system in Bangladesh. This descriptive cross sectional study with a mixed quantitative and qualitative design aimed to explore the opportunities and challenges of nurses after upgradation of class 2 status. The study was carried out in two specialized public hospitals for one year duration among purposively selected 144 nurses with a semi structured interview administered questionnaire In depth interview and focus group discussion (FGD) were conducted among selected personnel. The study revealed that the mean age of nurses was 42.3 (±6.3) years, majority (86.1%) were female, most of them (79.1%) were senior staff nurse with 16.8 years mean working experience. The study explored the opportunities of nurses after upgradation of class 2 status like increased responsibilities and honor in working place, promotional opportunities mentioned by majority of respondents. On the other hand, the challenges were noted as not changing the physicians attitude, not changing the working environment, limited scope for utilization of professional skill, not having job security mentioned by majority of respondents. The study also found that most of the nurses (90.3%) were satisfied after upgradation, but a large portion were not satisfied regarding fringe benefits and current salary structure. From FGD and in depth interview some suggestions come forward for nursing profession empowerment like good salary package, medical incentive, residence and training facilities etc. Few opportunities increased in upgradation of nurses in class 2 status, however nurses were depriving from many of their facilities, which indicated that 2nd class status was partially implemented in professionally, socially and culturally.Bangladesh Journal of Medical Education Vol.13(1) January 2022: 20-26